2008
DOI: 10.3390/entropy-e10020100
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation and Human Aging: Lifespan Entropy and Effect of Physical Activity Level

Abstract: Abstract:The first and second laws of thermodynamics were applied to biochemical reactions typical of human metabolism. An open-system model was used for a human body. Energy conservation, availability and entropy balances were performed to obtain the entropy generated for the main food components. Quantitative results for entropy generation were obtained as a function of age using the databases from the U.S. Food and Nutrition Board (FNB) and Centers for Disease Control and Prevention (CDC), which provide ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 18 publications
3
88
0
1
Order By: Relevance
“…Exergy analysis of biological processes is a relatively new subject. There are limited applications for cellular processes (Silva and Annamalai, 2008;Ketzer and de Meis, 2008;Lems et al 2009;The and Lutz, 2011;Mady et al 2012;Mady and de Olivera Jr., 2013;Genç et al, 2013a;Sorgüven and Özilgen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Exergy analysis of biological processes is a relatively new subject. There are limited applications for cellular processes (Silva and Annamalai, 2008;Ketzer and de Meis, 2008;Lems et al 2009;The and Lutz, 2011;Mady et al 2012;Mady and de Olivera Jr., 2013;Genç et al, 2013a;Sorgüven and Özilgen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By setting · I = 0 in above equation one can show that total optimum work rate is equal to sum of optimum work of each macro-nutrient · W ATP,opt = ∑ n · m n,reacted |∆G c,n |, whole body, n = CH, F and P where · m n,reacted , the consumption rate of nutrients which could be less than · m n,i and unreacted Gibbs function of nutrients at inlet and exit cancel out. Silva and Annamalai [8] found that the availability efficiency (η Avail = work delivered/optimum work) used in thermodynamics for an isothermal system is same as metabolic efficiency in biology. Thus, metabolic efficiency (η Met )…”
Section: Homogeneous Approachmentioning
confidence: 99%
“…Since the engineering studies for several fuels revealed that the ratio of change in Gibbs function to heating values of fuels/nutrients, | ∆G • c, n |/HV n ≈ C g , a constant ≈ 0.95 − 1.05 [8,16] for most nutrients. Hence |∆G c,n | * 1 − η Met,n ≈ C g HV n 1 − η Met,n where HV n is the heating value of nutrient n. Thus, after dividing by m B , Equation (6) becomes…”
Section: Homogeneous Approachmentioning
confidence: 99%
See 2 more Smart Citations